Vanishing ethnomedicinal wisdom: A survey of indigenous plant-based healing in Rangamati, Bangladesh - Ope, Solayman; Rafin, Rehtamim; W. Bussmann, Rainer; Ashrafuzzaman, M. (Ethnobotany Research and Applications, 2026)
Background: This study documents and evaluates the ethnomedicinal knowledge practiced by Baiddya healers in Rangamati district of the Chittagong Hill Tracts, Bangladesh, with the aim of assessing the traditional relevance of medicinal plants and examining their scientific justification through pharmacological evidence. Methods: Ethnobotanical data were collected between 5 January and 7 February 2025 using semi-structured interviews, guided field observations, and participatory plant walks involving fifteen experienced Baiddyas representing the Chakma, Marma, and Tanchangya communities. Results: A total of sixty-five medicinal plant species belonging to sixty-one genera and thirty-nine families were recorded. Zingiberaceae, Acanthaceae, Lamiaceae, and Araceae were the most frequently represented families. Comparative analysis with published pharmacological literature revealed that approximately sixty to seventy percent of the documented species showed moderate to strong scientific validation corresponding to their traditional uses, particularly for gastrointestinal, dermatological, respiratory, and infectious conditions. Well-established medicinal plants such as Curcuma longa, Aloe vera, Aegle marmelos, Justicia adhatoda, and Tinospora cordifolia demonstrated high translational relevance. Conclusions: The findings indicate that ethnomedicinal knowledge in Rangamati constitutes an empirically grounded healthcare system with significant potential for contributing to modern natural-product drug discovery. Preservation and scientific integration of this indigenous knowledge are essential for both cultural sustainability and future pharmacological innovation. Keywords: Ethnomedicine; medicinal plants; Rangamati; Bangladesh; pharmacological validation; Baiddya